Ciclização cascata de o-diinil benzyl calcogenetos promovida por dicalcogenetos de diorganoíla e FeCl3 - Pinheiro, Roberto do Carmo (2019)
The treatment of ortho-diynyl benzyl chalcogenides with a mixture of iron(III) chloride and diorganyl diselenides led to functionalized chalcogen isochromene-fused chalcogenophene derivatives. The reaction parameters were studied and the results indicated that the reaction of ortho-diynyl benzyl chalcogenides (0.25 mmol) with iron(III) chloride (2.0 equiv) and diorganyl diselenide (2 equiv) under reflux of dichloroethane was the best condition to give the products in 40-83% yields. The results support the idea that a mixture of iron salts and diorganyl diselenides has a dual action, promoting the cyclization and introducing a new functionalization at the 3-position of isochalcogenochromenes. The methodology was highly regioselective, giving the product via 6-endo-dig mode followed by a second cyclization via 5-endo-dig mode.